Estudo in silico e caracterização dos efeitos cardiovasculares do mononitrato orgânico 1,3- diisobutoxipropan-2-ila (NDIBP) em ratos normotensos e hipertensos - Cavalcanti, Airlla Laana de Medeiros (2021)
Organic nitrates are widely used to restore the levels and mimic the function of the endogenous nitric oxide (NO) reduced by endothelial dysfunction presented in arterial hypertension (AH). However, most of these drugs available for clinical use produce harmful side-effects, especially tolerance. The development of organic nitrates that do not present these drawbacks is still desired. This study aimed to investigate the new organic nitrate 1,3-diisobutoxypropan-2-yl (NDIBP) as an alternative for hypertension treatment, describing its synthesis, the biological and pharmacokinetic in silico potential, its vasculare effects, mechanism of action, acute toxicity, ability to induce tolerance, and its action on the cardiovascular system of normotensive and hypertensive rats. NDIBP was synthetized from glycerin by organic synthesis and characterized by Fourier-transform infrared spectroscopy and nuclear magnetic resonance spectra, obtaining an 85.7% yield. Biological activity spectrum was obtained by PASS (Prediction of Activity Spectra for Substances) revealing that the highest probable activities for NDIBP were related to cardiovascular actions such as antihypertensive and vasodilator effect. Drug-like properties and ADMET studies were carried out by pkCSM (Predicting Small-Molecule Pharmacokinetic Properties Using Graph-Based Signatures) software. Physicochemical parameters and ADMET prediction suggested that NDIBP presented a good theoretical oral bioavailability, good absorption in the gastrointestinal tract, and a low distribution in the tissues. In vitro chemiluminescence studies and ex vivo techniques showed that NDIBP released NO both in a cell-free system under anaerobic conditions and isolated mesenteric arteries through a metabolization process catalyzed by the enzyme xanthine oxidoreductase (XOR). In ex vivo experiments using rat mesenteric artery rings, NDIBP evoked an endothelium-independent vasorelaxation (Emax = 105.97 ± 3.65% vs. 91.78 ± 4.08 %, respectively, p < 0.05) significantly attenuated in the presence of PTIO (Emax = 66.22 ± 5.22 %, p < 0.05), ODQ (Emax = 26.22 ± 3.32 %, p < 0.05), TEA (Emax = 78.43 ± 3.55, p < 0.05), febuxostat (Emax = 69.96 ± 4.31 %, p < 0.05), and proadifen (Emax = 52.88 ± 3.04 %, p < 0.05). Furthermore, this organic nitrate was not able to induce tolerance in the vessel and presented a low oral acute preclinical toxicity. In vivo alterations on cardiovascular parameters were assessed using normotensive and renovascular hypertensive rats. NDIBP induced a hypotensive effect and a dual action in the heart rate that were significantly higher in hypertensive animals than in normotensive. Our results indicated that NDIBP possesses good in silico biological activities and drug-like properties and acts as a new NO donor, acute hypotensive and bradycardic agent, and is a non-self-tolerant organic nitrate, developing vasorelaxation through NO release, activation of NOsGC- cGMP pathway, and positive modulation of K+ channels in vascular smooth muscle. Therefore, all the data suggest that NDIBP is a good candidate for further investigation in the treatment of arterial hypertension and drug development studies.